Hyperbaric Oxygen: Therapy for Patients With Maxillofacial Implants? - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Danelon, Marcelle; Pesqueira, Aldieris Alves [UNESP]; Dekon, Stefan Fiuza de Carvalho [UNESP]; Fajardo, Renato Salviato [UNESP] (Lippincott Williams & Wilkins, 2009)
Osseointegration was an innovative treatment in dentistry during the last 3 decades. The success of osseointegration is related to factors such as material biocompatibility, adequate quality of bone tissue that allows implantation, surgical technique, and macrostructure and microstructure of implant. The osseointegrated implants are successfully applied in dental clinic including oral and facial rehabilitations mainly for patients submitted to mutilating surgeries. However, patients submitted to radiation therapy present risks to treatment with implants owing to adverse effects on bone tissue. Nowadays, the literature suggests different therapies to improve the success of osseointegration such as hyperbaric oxygen therapy that aims to prepare bone and adjacent tissues to receive the implant. Therefore, the purpose of this study was to present a literature review concerning indications, contraindications, successes, and difficulties with hyperbaric oxygen therapy associated to maxillofacial implants.
Keywords: Hyperbaric oxygen; maxillofacial implants; irradiated; oncology